Monte Carlo simulations of vehicle-mounted whole-body NaI(Tl) counter. (1st September 2022) - Mo, H.; Gong, P.; Liang, D.; Wang, Z.; Zhang, J.; Hu, Z.; Wu, R.; Tang, X.; Wang, J.; Ma, J.; Yang, X.
Abstract: During a nuclear emergency, an internal exposure detection device with on-site and rapid measurements should be developed to assess the level of internal exposure of people in radioactively contaminated areas. Based on MCNP simulations, this work designed a shielding structure of a NaI(Tl) type vehicle-mounted whole-body counter (VM-WBC) and it has good shielding performance against the background radiation. The mass of the shielding structure was less than 800 kg, and the minimum detectable activity (MDA) of 60 Co and 137 Cs obtained by simulation for a 10 min measurement was less than 50 Bq. And we also study its counting efficiency calibration by simulating radiation computing phantoms with Chinese and American reference physiological characteristics. Equations that fit counting efficiency, body build index, and photon energy were also developed. The relative efficiency deviation between the equation and the MCNP simulation was less than 5%.